Note—On “A Parsimonious Description of the Hendry System” - Rubinson, Joel R.; Vanhonacker, Wilfried R.; Bass, Frank M. (Management Science, 1980)
The Hendry market structure and partitioning theory and methodology are explained and contrasted with a strictly empirical approach in this note.